The Influence of Taxpayer Awareness and Tax Incentives on Compliance in Paying Land and Building Tax (PBB) in Bekasi City in 2022-2024 - Sri Yanti; Bella Puspita Audina; Abdillah Abdillah (Indonesian Economic Review, 2026)
Land and Building Tax is a potential source of regional revenue. This study aims to analyze the influence of taxpayer awareness and tax incentives on taxpayer compliance. The research method used a quantitative approach with a Likert-scale survey of 384 respondents. Data analysis was conducted using Pearson correlation tests, multiple linear regression, t-tests, F-tests, and the coefficient of determination (R²) using SPSS version 20. The results showed that taxpayer awareness and tax incentives simultaneously had a significant effect on taxpayer compliance (F = 314.023; p < 0.05). Partially, taxpayer awareness and tax incentives had a positive and significant effect on taxpayer compliance. The correlation test showed a positive and significant relationship between each independent variable and taxpayer compliance. The R² value of 0.622 indicates that 62.2% of taxpayer compliance can be explained by taxpayer awareness and tax incentives. In conclusion, taxpayer awareness and tax incentives play a significant role in increasing taxpayer compliance.